2022
DOI: 10.1039/d2cp00670g
|View full text |Cite
|
Sign up to set email alerts
|

Strain modulation of the exciton anisotropy and carrier lifetime in black phosphorene

Abstract: Manipulating exciton is of great significance to explore the optical properties of 2D materials. In this work, we investigate the excitonic properties and carrier dynamics of bilayer black phosphorene by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…It has been reported that the carrier injection through interface I is negligible in MoS 2 FETs with Au electrodes in monolayer limits because the region of the MoS 2 film under the contact is depleted [34]. By contrast, considerable contributions from both the two trajectories are found in the ML arsenene FETs with metallic multilayer arsenene electrodes [35] and in ML black phosphorene (BP) FETs with BN-Ni electrodes [36]. Therefore, both the vertical and lateral SBs are analyzed in 2DSC transistors in this paper.…”
Section: Structure Of Schottky Barrier In a 2d Fetmentioning
confidence: 99%
“…It has been reported that the carrier injection through interface I is negligible in MoS 2 FETs with Au electrodes in monolayer limits because the region of the MoS 2 film under the contact is depleted [34]. By contrast, considerable contributions from both the two trajectories are found in the ML arsenene FETs with metallic multilayer arsenene electrodes [35] and in ML black phosphorene (BP) FETs with BN-Ni electrodes [36]. Therefore, both the vertical and lateral SBs are analyzed in 2DSC transistors in this paper.…”
Section: Structure Of Schottky Barrier In a 2d Fetmentioning
confidence: 99%
“…A finite-sized heterostructure of 6L-hBN/4L-BP/6L-hBN was considered for mechanical and quantum interactions between BP and hBN layers to ensure a reasonable computational cost for practical ab initio simulations. The band structure was calculated with the optB86b-vdW functional, which reveals a direct band gap at the Γ point, as reported in previous studies for bulk and few-layer BP 27,35,36 . The optB86b-vdW functional was utilized because it can reliably predict both the electronic structure and phonon dispersion of the hBN/BP/hBN heterostructure and bulk hBN, whereas the LDA functional severely underestimates the band gap of 2D vdW materials (Supplementary Fig.…”
Section: First Principles Simulationmentioning
confidence: 79%
“…For example, BP/ TiO 2 heterojunction contributed to efficient exciton dissociation and interfacial charge separation, which is reflected in the H 2 generation rate of the BP/TiO 2 heterojunction, which is 2.4 times higher than that of pure TiO 2 . 127 Additionally, the electronic structure of BPs can be tailored by other structural modifications including strain, 128 elemental doping, 129 and field enhancement. 130 Owing to the atomically low thickness, excitons are tightly bound in monolayer TMDs (especially MoS 2 ) and dominate their optical properties.…”
Section: Other Low-dimensional Exciton Systemmentioning
confidence: 99%